COVID-19 Pandemic Impacts on the Mental Health of Professional Soccer: Comparison of Anxiety Between Genders - Esteves, Natã Sant’Anna; Brito, Michele Andrade de; Müller, Vanessa Teixeira; Brito, Ciro José; Valenzuela Pérez, Diego Ignacio; Slimani, Maamer; Bragazzi, Nicola Luigi; Miarka, Bianca (Frontiers in Psychology, 2021)
This study verifies associated factors with trait and state anxiety in professional soccer teams during the COVID-19 pandemic. The sample was composed of 315 athletes, coaches, and physical trainers of professional soccer teams during the COVID-19 pandemic. From this amount, 214 were classified with trait anxiety, and 315 were classified with state anxiety using the State-Trait Anxiety Inventory (STAI). This study is an epidemiological and cross-sectional study. We applied an observational method, and we performed a remote measurement. The measurement was made via online questionnaires in male and female individuals working on soccer teams (soccer professionals or athletes) who could be affected by anxiety during social isolation in the COVID-19 pandemic. Each questionnaire was composed of sociodemographic questions, self-perceived performance, and State-Trait Anxiety Inventory (STAI). The main results indicated a significant difference between female vs. male soccer professionals in state anxiety (54.97±9.43 vs. 57.65±9.48 index) and trait anxiety (54.21±5.74 vs. 55.76±6.41 index) with higher results in men. Sociodemographic variables impacted significant differences between female and male athletes and professionals of soccer clubs, and anxiety during the pandemic COVID-19 period impacted self-perceived performance analysis. The present results highlight the importance of cognitive behavior therapy for professional soccer teams.